Discovery of an antibody for pan-ebolavirus therapy - Furuyama, Wakako (Sci Rep, 2016)
During the latest outbreak of Ebola virus disease in West Africa, monoclonal antibody therapy (e.g., ZMapp) was utilized to treat patients. However, due to the antigenic differences among the five ebolavirus species, the current therapeutic monoclonal antibodies are only effective against viruses of the species Zaire ebolavirus. Although this particular species has indeed caused the majority of human infections in Central and, recently, West Africa, other ebolavirus species (e.g., Sudan ebolavirus and Bundibugyo ebolavirus) have also repeatedly caused outbreaks in Central Africa and thus should not be neglected in the development of countermeasures against ebolaviruses. Here we report the generation of an ebolavirus glycoprotein-specific monoclonal antibody that effectively inhibits cellular entry of representative isolates of all known ebolavirus species in vitro and show its protective efficacy in mouse models of ebolavirus infections. This novel neutralizing monoclonal antibody targets a highly conserved internal fusion loop in the glycoprotein molecule and prevents membrane fusion of the viral envelope with cellular membranes. The discovery of this highly cross-neutralizing antibody provides a promising option for broad-acting ebolavirus antibody therapy and will accelerate the design of improved vaccines that can selectively elicit cross-neutralizing antibodies against multiple species of ebolaviruses.